LIBERALIZING ABORTION LAWS IN SRI LANKA; PROSPECTS AND CHALLENGES - Thilakarathna, K.A.A.N. (Sri Lanka Journal of Forensic Medicine, Science & Law, 2018)
Abortion is legally defined as the removal of the fetus from the uterus any time before its gestation is completed. The law governing abortions in Sri Lanka is contained in the Penal Code Ordinance No 02 of 1883. According to section 303 of the code, abortion is only permitted when carried out to save the mother’s life. Sri Lanka is a country with the most restrictive laws on abortions in the south Asian region along with Afghanistan. However, even with these restrictions it is estimated that, Sri Lanka has one of the highest abortion rates in the world. Many attempts have been made to reform the penal laws relating to abortions which were enacted in colonial times. This includes the initiative taken by the law commission of Sri Lanka in 2013 when they proposed rape and foetal impairment as grounds for legal abortion. However, no actions have been taken regarding the liberalization of the provisions pertaining to abortions. A qualitative approach was used to identify the prospects and challenges that lie ahead in liberalizing the laws of abortions. Initial inquiry revealed that religious and cultural reasons account for the strict opposition towards liberalization which has negatively affected the political will of the rulers in bringing about changes. The greatest fear has been that liberalization would result in a sudden increase in the number of abortions. However, studies have revealed that, liberalization does not increase abortion rates but helps reduce the number of fatalities resulting from unsafe illegal abortions. The liberalization of the abortion laws has become both a contemporary and a necessary change for the protection and enhancement of the rights of women and their autonomy.
Keywords: LIBERALIZING ABORTION LAWS IN SRI LANKA; PROSPECTS AND CHALLENGES